SARS-CoV-2 Viral Load Has an Impact on Cytokine Storm in Severe COVID-19 Patients - Al-Nuaimi, Bareq N.; Al-azzawi, Raghad H. (Iraqi Journal of Science, 2026)
Viral load is a topic of interest among researchers, especially to estimate COVID-19’s severity. The current research is performed to demonstrate the correlation between the viral load of SARS-CoV-2 in hospitalized patients and cytokine storm progression. A case-control study has been conducted from October 2022 to June 2023. Nasopharyngeal samples were taken from 89 patients for the assessment of the SARS-CoV-2 viral load. The virus was detected and quantified by molecular tests employing real-time polymerase chain reaction (qPCR). Serological assays were also done for the determination of inflammatory cytokine levels (IL-6, IL-8, and IL-1β) in the blood and the estimation of some biomarkers of inflammation (C-reactive protein, D-dimer, and ferritin). Fifty random samples of severe COVID-19 and forty mild cases of COVID-19 and apparently healthy individuals as a control group were selected for this purpose. The multiplexed RT-PCR confirmed the positive samples by detecting the ORF1ab gene of the virus. Viral load results reveal a range from one thousand (103) to one million (106) copies/ml of the virus in each sample depending on Ct values (a final dynamic range of 3.00 to 6.289 log10 copies/ml and an average of 4.425 log10 copies/ml). The inflammatory cytokines (IL-6, IL-8, and IL-1β) and inflammatory biomarkers (CRP, D-dimer, and ferritin) were increased during the disease. The correlation between log10 viral load and cytokine storm markers was positive. The number of viral particles present may impact the cytokine storm progression and extend the duration hospital stay.